As experiências comunicacionais e identitárias ribeirinhas amazônicas por meio do consumo do chocolate da marca Filha do Combu - MORAES, Giselle do Carmo Souza (Universidade Federal do Pará, 2024)
This research seeks to investigate the consumption of chocolate from Ilha do Combu in the city of Belém, in the state of Pará, as a mediator of communication experiences of Amazonian riverside identity, focusing the analysis on communication and consumption strategies in the brand Filha do Combu, a company located in Combu and owned by Izete Costa, Dona Nena, as she is popularly known. For this research the following methodologies were used: participant observation, carried out at the point of sale, to gain insights about the strategies of dissemination, sales and some of the consumer behaviors; interviews with the administrative and strategic sector of the company; netnography, in order to collect and analyze online information about the company and its target audience; analysis of communicational material of the company's printed and digital content, especially in the digital social network Instagram and the website www. The study is based on the analysis of the processes of origin, production and dissemination of chocolate, as well as of other products and experiences offered by Filha do Combu, and of the strategies of construction and dissemination of the brand Filha do Combu when inserting, in its communicative, consumption and brand building actions, concepts of sustainability, ambientability and experience marketing. The research also presents some of the challenges and marketing negotiations that the company carries out when considering how the consumption of Combu's chocolate can awaken affective memories and media representativeness, which ends up demarcating and building concepts, values and status represented by the company and makes use of the market differentials arising from the brand itself represented by the Amazon.